1022 Evergreen Place - Macomber, Debbie (Don Mills, Ont. : Mira Books, 2010)
Neighbors Mary Jo Wyse and Mack McAfee feel their love grow as they work together to solve the mystery of what happened to the World War II soldier who wrote the letters that Mary Jo found, and to the girl he wrote to.
Keywords: Man-woman relationships; Community life; Cedar Cove (Wash. : Imaginary place); City and town life -- Washington (State); Washington (State); Domestic fiction; Love stories